Primary germ cell tumor of the liver - Mayara Caroline Amorim Fanelli; Alexandre Alberto Barros Duarte; Fernanda Kelly Marques de Souza; Amanda Soares de Medeiros; Carla Renata Pacheco Donato Macedo; Maria Teresa de Seixas Alves; Henrique Manoel Lederman; Simone Campos Vieira Abib (Elsevier, 2019)
Introduction: Germ cell tumors may present in various forms and sites, that may be gonadal or extragonadal. Extragonadal tumors are more frequent in children and can occur in the sacrococcygeal region, retroperitoneum, mediastinum, neck and pineal gland. Primary germ cell tumors of the liver are extremely rare. Currently, there are few cases described in the literature, without consensus proposals for treatment. Objectives: To describe the case of a patient with a primary germ cell tumor (GCT) of the liver associated with Primary Sclerosin Cholangitis (PSC), discuss the diagnosis and surgical challenges, and to perform a comparative analysis with similar cases already published in the literature. Case report: 13-year-old female with Primary Sclerosing Cholangitis (PSC) was diagnosed with an hepatic tumor and had a mixed GCT with components of an endodermal sinus tumor and an embryonal carcinoma in the histological analysis. The patient was treated surgically, followed by systemic chemotherapy. Conclusion: GCT primary of the liver must be considered in the differential diagnosis of liver tumors. Keywords: Germ cell tumor, Liver tumor, Childhood tumor